Scilab: A Free Software to Matlab - Hema Ramachandran (S. Chand & Company, 2012)
This book is a comprehensiv\'s primer on SCILAB (A Free Software alternative to MATLAB) hailed very often as the language of technical and scientific computing. MATLAB has found a permanent place not only in curriculum of Applied Science and Engineering Studies, but also in Research and Development Arena. SCILAB closely mimics functionalities of MATLAB and is emerging to be an effective alternative.